2010
DOI: 10.1007/s00534-010-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

A new classification for hepatocellular carcinoma with portal vein tumor thrombus

Abstract: In patients with HCC with macroscopic PVTT treated by partial hepatectomy with or without thrombectomy, our PVTT classification better stratified and predicted prognosis than the TNM staging, CLIP scoring system, and JIS scoring system, which were unrefined and inadequate for this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
147
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 12 publications
1
147
1
1
Order By: Relevance
“…these data, miR-155 appears to be involved in tumor progression through the inhibition of multiple tumor suppressor genes, such as sex-determining region Y-gene related high-mobility-group box gene (24,25) and suppressor in cytokine signaling 1 (26), thus promoting proliferation and invasion in HCC. Surgical resection is the typical initial treatment for primary liver cancer (27). This previous demonstrated that the rate of HCC surgery recurrence rate was significantly increased within 1 year of surgery and was accompanied by poor prognosis, compared with the recurrence rate in subsequent years.…”
Section: Discussionmentioning
confidence: 99%
“…these data, miR-155 appears to be involved in tumor progression through the inhibition of multiple tumor suppressor genes, such as sex-determining region Y-gene related high-mobility-group box gene (24,25) and suppressor in cytokine signaling 1 (26), thus promoting proliferation and invasion in HCC. Surgical resection is the typical initial treatment for primary liver cancer (27). This previous demonstrated that the rate of HCC surgery recurrence rate was significantly increased within 1 year of surgery and was accompanied by poor prognosis, compared with the recurrence rate in subsequent years.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Child-Pugh class C liver function were not considered for resection. 22 Based on the location and extent, PVTT was classified into 4 types according to the study by Shi et al 25 Original Article Type I: tumor thrombi involving the segmental branches of the portal vein or above; type II: tumor thrombi extending to involve the right/left portal vein; type III: the main portal vein; type IV: the superior mesenteric vein. The presence of PVTT was confirmed histopathologically in the resected specimens in the HR group.…”
Section: Patientsmentioning
confidence: 99%
“…In 2007, Shi et al (11) proposed a PVTT classification which was based on the extent of the tumor thrombus in the portal vein, as follows: Type I0, tumor thrombus formation found under microscopy; type I, tumor thrombi involving segmental branches of portal vein or above; type II, tumor thrombi involving right/left portal vein; type III, tumor thrombi involving the main portal vein trunk; and type IV, tumor APTT, activated partial thromboplastin time; HBs, hepatitis B surface; HCV, hepatitis C virus; AFP, α-fetoprotein; CEA, carcinoembryonic antigen; AST, aspartate aminotransferase; ALT, alanine aminotransferase; ALP, alkaline phosphatase; γGTP, γ-glutamyl transpeptidase; LDH, lactate dehydrogenase; Na, sodium; K, potassium; Cl, chlorine; BUN, blood urea nitrogen; Cr, creatinine.…”
Section: Discussionmentioning
confidence: 99%